Institutional protocol to standardize the chest drainage system management, from surgery to nursing care, at a regional hospital in northern Paraná - Amanda Carina Coelho de Morais; Maurício Medeiros Lemos; Vlaudimir Dias Marques; César Orlando Peralta Bandeira (Universidade Estadual de Maringá, 2016)
The purpose of chest drainage is to allow lung re-expansion and the reestablishment of the subatmospheric pressure in the pleural space. Properly managing the drainage system minimizes procedure-related complications. This prospective observational study evaluated adult patients undergoing water-seal chest drainage, admitted to our hospital and accompanied by residents and tutors, aiming to check their care. One hundred chest drainages were monitored. The average age was 38.8 years old. The average drainage time was 6.7 days. Trauma was the prevalent cause (72%) for the indication of pleural drainage. The obstruction of the system occurred in 6% of the cases; 5% subcutaneous emphysema, 1% infection around the drain; 5% accidental dislodgement of the drain, and in 5% of the patients, there were some complications when removing the drain. Failures in chest drainage technique and management were present, and reflected in some complications that are inherent to the procedure, although it is known that there are intrinsic complications. This study aimed to assess the management of closed chest drainage systems and standardize the care provided in such procedure.